Entre o matrimônio, a beleza, a moda e esportes : imagens da mulher na Revista Vida Capichaba (1925-1939) - Silva, Cecília Nunes da (2014)
The objective of this dissertation is to investigate the images of feminine in the magazine Vida Capichaba, a periodical published biweekly in the State of Espirito Santo, Brazil, between the decades of 1920 and 1950. Due to the magazine’spublication longevity, the authors decided to focus on the decades of 1920 and 1930, particularly between 1925 and 1939. It was found out that the woman ideal present in that magazine went through both the construct of moral requisites and an appropriate education to play roles known to be naturally feminine, such as marriage and maternity. Beside this characteristic, other practices were even more emphasized. The construct of beauty, of a thin and young body associated with the valorisation of sport and fashion became characteristics of the new woman of Espirito Santo. Efficiency and delicacy, sensuality and obedience, maternity and independance, agility and elegance, beauty and freedom. It is in such dualities that traditional social codes and new cultural values fit together, defining new ways of being, which composed the frame work of images in the magazine Vida Capichaba.